2009
DOI: 10.1007/s12010-009-8736-3
|View full text |Cite|
|
Sign up to set email alerts
|

Enhancing the Enzymatic Hydrolysis of Corn Stover by an Integrated Wet-milling and Alkali Pretreatment

Abstract: An integrated wet-milling and alkali pretreatment was applied to corn stover prior to enzymatic hydrolysis. The effects of NaOH concentration in the pretreatment on crystalline structure, chemical composition, and reducing-sugar yield of corn stover were investigated, and the mechanism of increasing reducing-sugar yield by the pretreatment was discussed. The experimental results showed that the crystalline structure of corn stover was disrupted, and lignin was removed, while cellulose and hemicellulose were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 22 publications
1
18
0
Order By: Relevance
“…However, our results also showed that if lignin is the target at this stage, all three pretreatments, NaOH 1.5% alone, NaOH 2% alone and NaOH 1.5% with crude enzyme can be efficient. This was in good agreement with the study of He et al, 53 who reported that increase in NaOH concentration from 1% to 2% did not significantly improve delignification of corn straw.…”
Section: Pretreatment Of Corn Stalksupporting
confidence: 93%
“…However, our results also showed that if lignin is the target at this stage, all three pretreatments, NaOH 1.5% alone, NaOH 2% alone and NaOH 1.5% with crude enzyme can be efficient. This was in good agreement with the study of He et al, 53 who reported that increase in NaOH concentration from 1% to 2% did not significantly improve delignification of corn straw.…”
Section: Pretreatment Of Corn Stalksupporting
confidence: 93%
“…Optimal process conditions for enzymatic hydrolysis to high glucose included both high SC and low enzyme loading. This is a remarkable improvement over previous studies done with pretreated corn stover either at low SC (<10 %) or high enzyme loading (>10 FPU, equivalent to 30 mg EP/g glucan) to achieve higher cellulose conversion [5,6,18,19]. By increasing the SC, the glucose yield improved significantly.…”
Section: Influence Of Sc and Enzyme Loading During Enzymatic Hydrolysismentioning
confidence: 64%
“…1. Unlike the SSF process in previous works, ours does not use pretreated corn stover samples [13,19,25,42] or the addition of expensive commercial enzymes [12,26,53]. Instead, cellulases and hemicellulases are produced by G. trabeum and P. chrysosporium in situ upon corn stover enzyme induction performed via solid substrate fermentation in a pH range of 4.5-4.8 at 37 o C for 4 days, conditions that are suitable not only for the growth of the fungi but also for production of cellulolytic enzymes [38,43,44].…”
Section: Enzyme Induction On Untreated Corn Stovermentioning
confidence: 99%
“…Pretreatment of plant biomass is crucial for the production of cellulosic ethanol as it greatly improves the enzymatic accessibility of the feedstock [13,19,25,41,42]. In recent years, several pretreatment methods have been tested on corn stover that involve physical, chemical, or physicochemical procedures or a combination thereof [16,47,56].…”
mentioning
confidence: 99%